Oblicz wartość wyrażenia: [latex] frac{( x^{2} y^{3}) ^{2}* (-3 x^{3} y^{2})^{3} }{ (-x y^{2}) ^{5} } [/latex] dla x=[latex] sqrt{3} [/latex] , y=[latex] frac{1}{9} [/latex]

Oblicz wartość wyrażenia: [latex] frac{( x^{2} y^{3}) ^{2}* (-3 x^{3} y^{2})^{3} }{ (-x y^{2}) ^{5} } [/latex] dla x=[latex] sqrt{3} [/latex] , y=[latex] frac{1}{9} [/latex]
Odpowiedź

[latex] frac{ sqrt{3^4}* frac{1}{9^{12}} * (-3* sqrt[]{3^9} ) }{ - sqrt{3^5} * frac{1}{9^{10}} } = frac{9 * (-3) * sqrt[]{3^{9}} }{- sqrt{3^5} } * frac{1}{9^2} = -27 * (-9) * frac{1}{81} = 27[/latex]

Dodaj swoją odpowiedź